Preparation, Characterization, Thermal, and Dielectric Properties of Polypyrrole/h-BN Nanocomposites - DUMLUDAĞ, FATİH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (WILEY-HINDAWI, 2014)
The aim of this study was to improve thermal stability and dielectric properties of polypyrrole (PPy) by adding hexagonal boron nitride (h-BN). PPy was synthesized, and PPy/h-BN nanocomposites were prepared by adding various proportions of h-BN to PPy. The chemical structures of the samples were investigated by Fourier transform infrared spectroscopy. Thermal properties of the nanocomposites were determined by thermogravimetric analysis and differential scanning calorimetry. X-ray diffraction analysis of the samples was carried out. The surface morphologies of the samples were investigated by a scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS). The obtained results prove that the nanocomposite system is more thermally stable than the pure PPy. Dielectric measurements revealed that the dielectric constant of the pellets increased with increasing temperature and decreased with increasing frequency. It is also observed that the dielectric constant of the pellets decreased with increasing nano-hBN content (between 1 and 4 wt%).
Keywords: Dielectric properties; Hexagonal boron nitride; Polypyrrole; INVERTED EMULSION PATHWAY; TRANSPORT-PROPERTIES; COMPOSITES; NANOPARTICLES; CONDUCTIVITY; DEGRADATION; POLYANILINE; ELECTRODES